Spontaneous Riboflavin-Overproducing Limosilactobacillus reuteri for Biofortification of Fermented Foods - Spacova, Irina; Ahannach, Sarah; Breynaert, Annelies; Erreygers, Isabel; Wittouck, Stijn; Bron, Peter A.; Van Beeck, Wannes; Eilers, Tom; Alloul, Abbas; Blansaer, Naïm; Vlaeminck, Siegfried E.; Hermans, Nina; et al. (Frontiers in Nutrition, 2022)
Riboflavin-producing lactic acid bacteria represent a promising and cost-effective strategy for food biofortification, but production levels are typically insufficient to support daily human requirements. In this study, we describe the novel human isolate Limosilactobacillus reuteri AMBV339 as a strong food biofortification candidate. This strain shows a high natural riboflavin (vitamin B2) overproduction of 18.36 µg/ml, biomass production up to 6x1010 colony-forming units/ml (in the typical range of model lactobacilli), and pH-lowering capacities to a pH as low as 4.03 in common plant-based (coconut, soy and oat) and milk beverages when cultured up to 72 h at 37°C. These properties were especially pronounced in coconut beverage and butter milk fermentations, and were sustained in co-culture with the model starter Streptococcus thermophilus. Furthermore, L. reuteri AMBV339 grown in laboratory media or a coconut beverage survived in gastric juice and in a simulated gastrointestinal dialysis model with colon phase (GIDM-colon system) inoculated with fecal material from a healthy volunteer. Passive transport of L. reuteri AMBV339-produced riboflavin occurred in the small intestinal and colon stage of the GIDM system, and active transport via intestinal epithelial Caco-2 monolayers was also demonstrated. L. reuteri AMBV339 did not cause fecal microbiome perturbations in the GIDM-colon system and inhibited enteric bacterial pathogens in vitro. Taken together, our data suggests that L. reuteri AMBV339 represents a promising candidate to provide riboflavin fortification of plant-based and dairy foods, and has a high application potential in the human gastrointestinal tract.